(3GdJhLjg GdOQGSj hGdegfj ddJdejP GddHfGfj aj fgGjI GdeQMdI GdeJhSWI (B((3bVGA cSQhGf(B)s - (3GdLVe, haGAs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2001)
(3JgOa gPg GdOQGSI Edi HjGf CKQ hLhO GdJhLjg GdOQGSj hGdegfj aj fgGjI eQMdI GdJYdje GdCSGSj NGUI eY ZjGH GdGNJUGUjjf aj eLGd GdJhLjg GdOQGSj hGdegfj(B. (3hbO GSJNOeJ GdOQGSI GdHMK GdejOGfj GdPj jJMbb HhGSWI GSJeGQI Je JeQjQgG Ydi JdGePI GdUa GdQGHY GdeJhSW aj HYV GdeOGQS GdQSejI hGdNGUI HTbjgG GdOjfj hGdYdeGfj(B. (3hNdUJ GdOQGSI Edi GdfJGFL GdJGdjI(B:1) (3Ef YOe eYQaI GdJdejP HTcd YGe HGdaQhY GdOQGSjI GdehLhOI YfO GdGfJgGA ef eQMdI GdJYdje GdCSGSj, jDOj Edi GNJjGQ OQGSJg hegfJg HTcd YThGFj hZjQ eJhGab eY WehMGJg GdeSJbHdjI(B. 2) (3Ef GdJdGejP dOjge ZGdHG ShA JbOjQ dbOQGJge hJdGDegG eY GdegfI GdeNJGQI hjYHQ gDdGA GdJdGejP Yf QZHJge aj Jdbj GdeSGYOI ef gPg GdfGMjI HGdJMOjO(B. 3) (3Ef GdCgd dge JCKjQ HGdZ Ydi NjGQGJ GdJdGejP aj HfGA eSJbHdge hjDcO GdJdGejP Ydi MGLJge Edi Phjge hGfUjGYge hQGA QZHGJ Phjge(B. (3hHOG Cf gfGc fbU aj GdfbGT Mhd gPG GdehVhY Hjf GdJdGejP hGdGgd(B. 4) (3jDcO GdJdGejP MGLJge Edi eQTO hehLg Pj GNJUGU heYQaI deSGYOJge Ydi eYQaI bOQGJge hejhdge ef LgI hGdeLGdGJ GdOQGSjI hGdegfjI ef LgI CNQi, hPdc HZjI GdJhUd Edi GNJjGQ jdGFe bOQGJge hejhdge aj Bf eYG(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle moyen; Intermediate Education; Keserouane; Keserouane; Orientation et Conseil; School guidance and counseling; (3GdJhLjg hGdEQTGO GdeOQSjs; (3GdeQMdI GdeJhSWIs; (3cSQhGfs